The Cutting Edge A Half Century of U.S. Fighter Aircraft R&D - Lorell, Mark A. (RAND Corporation, 1998)
The proposition that innovation is critical in the cost-effective design and development of successful military aircraft is still subject to some debate. RAND research indicates that innovation is promoted by intense competition among three or more industry competitors. Given the critical policy importance of this issue in the current environment of drastic consolidation of the aerospace defense industry, the authors here examine the history of the major prime contractors in developing jet fighters since World War II. They make use of an extensive RAND database that includes nearly all jet fighters, fighter-attack aircraft, and bombers developed and flown by U.S. industry since 1945, as well as all related prototypes, modifications, upgrades, etc. The report concludes that (1) experience matters, because of the tendency to specialize and thus to develop system-specific expertise; (2) yet the most dramatic innovations and breakthroughs came from secondary or marginal players trying to compete with the industry leaders; and (3) dedicated military R&D conducted or directly funded by the U.S. government has been critical in the development of new higher-performance fighters and bombers.